Sacubitril/valsartan ameliorates cardiac hypertrophy and preserves diastolic function in cardiac pressure overload. (26th January 2021) - Nordén, Einar Sjaastad; Bendiksen, Bård Andre; Andresen, Henriette; Bergo, Kaja Knudsen; Espe, Emil Knut; Hasic, Almira; Hauge‐Iversen, Ida Marie; Veras, Ioanni; Hussain, Rizwan I.; Sjaastad, Ivar; Christensen, Geir; Cataliotti, Alessandro
Abstract: Aims: Sacubitril/valsartan (sac/val) has shown superior effect compared with blockade of the renin–angiotensin–aldosterone system in heart failure with reduced ejection fraction. We aimed to investigate effects of sac/val compared with valsartan in a pressure overload model of heart failure with preserved ejection fraction (HFpEF). Methods and results: Sprague–Dawley rats underwent aortic banding or sham ( n = 16) surgery and were randomized to sac/val ( n = 28), valsartan ( n = 29), or vehicle ( n = 26) treatment for 8 weeks. Sac/val reduced left ventricular weight by 11% compared with vehicle ( P = 0.01) and 9% compared with valsartan alone ( P = 0.04). Only valsartan reduced blood pressure compared with sham ( P = 0.02). Longitudinal early diastolic strain rate was preserved in sac/val compared with sham, while it was reduced by 23% in vehicle ( P = 0.03) and 24% in valsartan ( P = 0.02). Diastolic dysfunction, measured by E/e'SR, increased by 68% in vehicle ( P < 0.01) and 80% in valsartan alone ( P < 0.001), while sac/val showed no increase. Neither sac/val nor valsartan prevented interstitial fibrosis. Although ejection fraction was preserved, we observed mild systolic dysfunction, with vehicle showing a 28% decrease in longitudinal strain ( P < 0.01). Neither sac/val nor valsartan treatment improved this dysfunction. Conclusions: In a model of HFpEF induced by cardiac pressure overload, sac/val reduced hypertrophy compared with valsartan alone and ameliorated diastolic dysfunction. These effects were independent of blood pressure. Early systolic dysfunction was not affected, supporting the notion that sac/val has the largest potential in conditions characterized by reduced ejection fraction. Observed anti‐hypertrophic effects in preserved ejection fraction implicate potential benefit of sac/val in the clinical setting of hypertrophic remodelling and impaired diastolic function.